PENGAJARAN MATERI PERPAJAKAN NPWP DAN NPPKP PADA SMK STRADA 1 - Lysander, Joshua Jose; Rasyid, Rosmita (Jurnal Serina Abdimas, 2024)
Taxation is a mandatory contribution from the citizens to the government based on laws, and it is coercive in nature, not receiving direct benefits (counterperformance) that can be immediately demonstrated and used to pay for general expenditure financing. The global world has experienced the COVID-19 pandemic, which has had a significant impact on the economy sector, resulting in many changes in tax regulations. The Teaching Assistance activity in Educational Units aims to improve the author's skills, both hard and soft skills, and provide taxation knowledge, especially on the subjects of Taxpayer Identification Numbers and Taxable Entrepreneur Confirmation Numbers to students. This activity is carried out at SMK Strada 1 for a total of 10 face-to-face meetings, starting from August 28, 2023, until October 5, 2023.The method of implementing the PKM (Community Service Program) used is to provide teaching through face-to-face meetings / offline and to incorporate some games related to the material.. The results of this activity show that students of SMK Strada 1 can easily understand the material taught and aim to increase the knowledge of the students of SMK Strada 1 regarding taxation subjects, especially the subjects of Taxpayer Identification Numbers and Taxable Entrepreneur Confirmation Numbers.